Faktor–Faktor yang Memengaruhi Tingkat Literasi Keuangan Syariah pada Mahasiswa Muslim di Bogor - Puspita, Amelia Tri; Lubis, Deni; Marhamah Muthohharoh (Department of Islamic Economics, IPB University, 2021)
The Indonesian Financial Services Authority (OJK) has targeted college students as one of the priority targets of their financial education programs in Indonesia. This research aimed to analyze the level of Islamic financial literacy of college students in Bogor; and analyze the factors that influence their level of Islamic financial literacy. The independent variable used in this study is the score of Islamic financial literacy. While gender, university, Grade Point Average (GPA), sources of information and religiosity are used as the dependent variables. The data analysis is conducted using the descriptive analysis and Structural Equation Modeling Partial Least Square (SEM-PLS). The estimation results showed that the level of Islamic financial literacy towards Muslim students in Bogor is 50.2% and is classified as sufficient literate. The study found that gender and university have positively and significantly influenced the level of Islamic financial literacy of Muslim students in Bogor.